2022
DOI: 10.7759/cureus.28033
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Stimulation for Treatment of Cluneal Neuropathy Case Study

Abstract: Chronic low back pain is a prevalent and sometimes debilitating condition. This case report describes a 69year-old female presenting with axial spine pain. The pain was inadequately controlled by opioids as she was treated unsuccessfully with hydrocodone and remained to have the pain between 7/10 and 10/10. Peripheral neural stimulation (PNS) was trialed and then used to control her pain. PNS is a device-based treatment option that appears effective in a subset of patients. It has been effectively used to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Historically, surgical decompression may be considered, targeting either the distal superior cluneal nerve branches or the involved lumbar radicular segments [3,4]. To reduce invasive therapies, previous case reports have shown that permanent PNS can provide relief for refractory SCN-induced LBP [5][6][7]. This case expands the option for SCN-induced LBP via a 60-day temporary PNS system, broadening the repertoire for patient care for sustained analgesic benefits compared to a permanent PNS system.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, surgical decompression may be considered, targeting either the distal superior cluneal nerve branches or the involved lumbar radicular segments [3,4]. To reduce invasive therapies, previous case reports have shown that permanent PNS can provide relief for refractory SCN-induced LBP [5][6][7]. This case expands the option for SCN-induced LBP via a 60-day temporary PNS system, broadening the repertoire for patient care for sustained analgesic benefits compared to a permanent PNS system.…”
Section: Discussionmentioning
confidence: 99%
“…They both demonstrated a refractory SCN case that was successfully treated with PNS. 11,12 Novel Approach to PNS for SCN In this section we will demonstrate a novel approach to placing a peripheral nerve stimulator for the superior cluneal nerve using a cadaver model and compare this new method to the current standard. This was a cadaveric study where placement was performed on a cadaver using fluoroscopic guidance with saving images to demonstrate all steps for placing a peripheral nerve stimulator introducer and lead.…”
Section: Peripheral Nerve Stimulation For Scnmentioning
confidence: 99%